Maturation of GABAergic Transmission in Cerebellar Purkinje Cells Is Sex Dependent and Altered in the Valproate Model of Autism - Roux, Sébastien; Lohof, Ann; Ben-Ari, Yehezkel; Poulain, Bernard; Bossu, Jean-Louis (Frontiers in Cellular Neuroscience, 2018)
The development of GABAergic signals includes receptor subunits reorganization, alterations of (Cl-)I levels and GABA depolarizing-excitatory/hyperpolarizing-inhibitory shift. This sequence is altered in animal models of autism stressing its relevance to disorders. Here, using cell-attached single GABAA receptor channel recordings in cerebellar Purkinje cells (PCs), we report the presence in males and females of two conductance levels (18 & 10 pS), the former being dominant in newborns and the latter in young-adults. The conductance shift like the depolarizing/excitatory to hyperpolarizing\inhibitory GABA shift occurred 4 days later in females than males. The conductance alterations like the GABA actions shifts were also delayed in valproate-treated mice. Our data support a parallel sex dependent developmental shift of GABA conductance and chloride gradient leading to distinct excitatory/inhibitory developmental sequences in males and females. The observation that these developmental sequences are deviated in autism further stresses the importance of correct timing in the pathogenesis of disorders.